Muscle wasting and adipose tissue browning in infantile nephropathic cystinosis. Issue 2 (7th September 2015) - Cheung, Wai W.; Cherqui, Stephanie; Ding, Wei; Esparza, Mary; Zhou, Ping; Shao, Jianhua; Lieber, Richard L.; Mak, Robert H.
Abstract: Background: Muscle wasting is a common complication in patients with infantile nephropathic cystinosis, but its mechanism and association with energy metabolism is not known. We define the metabolic phenotype in Ctns −/− mice, an established murine model of infantile nephropathic cystinosis, with focus on muscle wasting and energy homeostasis. Methods: Male Ctns −/− mice and wild‐type (WT) controls were studied at 1, 4, 9, and 12 months of age. As Ctns −/− mice started to develop chronic kidney disease (CKD) at 9 months of age, 9‐ and 12‐month‐old Ctns −/− mice were also compared with age‐matched WT mice with CKD. Serum and urine chemistry and energy homeostasis parameters were measured. Skeletal muscle histomorphometry and in vivo muscle function were measured. We studied expression of genes involved in muscle mass regulation, thermogenesis, energy metabolism, adipogenesis, and adipose tissue browning in Ctns −/− mice. Results: Ctns −/− mice showed loss of weight and lean mass and increased energy expenditure. Ctns −/− mice exhibited abnormal energy homeostasis before the onset of their CKD. Food intake in Ctns −/− mice was comparable with age‐matched WT controls. However, significantly lower total body mass starting at 1 month of age and increased energy expenditure at 4 months of age preceded the onset of CKD at 9 months of age in Ctns −/− mice. Muscle accept content in 1‐ and 4‐month‐old Ctns −/− mice was significantly lower than that in age‐matched WT controls. At 12 months of age, muscle fibre area and in vivo muscle strength was reduced in Ctns −/− mice than that in WT or CKD controls. Muscle wasting in Ctns −/− mice was associated with inhibition of myogenesis, activation of muscle proteolysis pathways, and overexpression of pro‐inflammatory cytokines. Increased energy expenditure was associated with elevation of thermogenesis in skeletal muscle and adipose tissues. The development of beige adipocytes in Ctns −/− mice is a novel finding. Expression of beige adipose cell surface markers (CD137, Tmem26, and Tbx1) and uncoupling protein‐1, which is a brown adipose tissue marker, was observed in inguinal white adipose tissue of Ctns −/− mice. Expression of key molecules implicated in the pathogenesis of adipose tissue browning (Cox2, cytochrome c oxidase subunit II; PGF2α, prostaglandin F2α; IL‐1α, interleukin 1α; IL‐6, interleukin 6; TNF‐α, tumor necrosis factor α) was significantly increased in inguinal white adipose tissue of Ctns −/− mice than that in WT controls. Conclusion: This study describes a mouse model of nephropathic cystinosis presenting with profound muscle wasting. The mechanism for hypermetabolism in Ctns −/− mice may involve up‐regulation of thermogenesis pathways in skeletal muscle and adipose tissues. This study demonstrates, for the first time, the development of beige adipocytes in Ctns −/− mice. Understanding the underlying mechanisms of adipose tissue browning in cystinosis may lead to novel therapy.